Analysis of Teaching Methods in the Classroom Inclusive For Increase Student Science Literacy Elementary school - Pertiwi, Ratih Purnama; Wasino, Wasino; Sumarni, Woro; Trimurtini, Trimurtini (Universitas Negeri Semarang, 2024)
Study This aims To analyze the effectiveness of various methods of teaching applied in class inclusive in increasing literacy of science students at the level of education base. Classroom inclusive is environment education where students need special Study together students regularly. Study This uses an approach qualitative with method studies involving cases in several schools the basis for applying it system class inclusive. Data is collected through observation class, interviews with teachers and students, and analysis document learning. Research results show that teaching collaborative and based projects effectively increases literacy science students in class. Approach This possible student with different abilities For Work the same and mutually helps understand scientific concepts. Additionally, the use tool visual aids and technology education has proven increase understanding student to the material science taught. Teachers who have understanding and skills manage class inclusive role important in successful method teaching them. This study concludes that combination method of teaching collaborative based projects and using technology can increase literacy science in a way significant among students in class inclusive. Recommendation for practitioners' education is to keep going develop and implement adaptive and inclusive teaching strategies To support diverse needs Study student.